Evaluating conservation dogs in the search for rare species. Issue 2 (3rd March 2020) - Bennett, Emma M.; Hauser, Cindy E.; Moore, Joslin L.
Abstract: Detecting rare species is important for both threatened species management and invasive species eradication programs. Conservation scent dogs provide an olfactory survey tool that has advantages over traditional visual and auditory survey techniques for some cryptic species. From the literature, we identified 5 measures important in evaluating the use of scent dogs: precision, sensitivity, effort, cost, and comparison with other techniques. We explored the scale at which performance is evaluated and examined when field testing under real working conditions is achievable. We also identified cost differences among studies. We examined 61 studies published in 1976–2018 that reported conservation dog performance, and considered the inconsistencies in the reporting of scent dog performance among these studies. The majority of studies reported some measure of performance; however, only 8 studies reported all 3 aspects necessary for performance evaluation: precision, sensitivity, and effort. Although effort was considered in 43 studies, inconsistent methods and incomplete reporting prevented meaningful evaluation of performance and comparison among studies. Differences in cost between similar studies were influenced by geographical location and how the dog and handler were sourced for the study. To develop consistent reporting for evaluation, we recommend adoption of sensitivity, precision, and effort as standard performance measures. We recommend reporting effort as the total area and total time spent searching and reporting sensitivity and precision as proportions of the sample size. Additionally, reporting of costs, survey objectives, dog training and experience, type of detection task, and human influences will provide better opportunities for comparison within and among studies. Abstract : Article impact statement : Key performance measures of the effectiveness of conservation scent dogs include precision, sensitivity, and effort. Abstract : Evaluación del Uso de Perros en la Conservación para la Búsqueda de Especies Raras Resumen: La detección de las especies raras es importante tanto para el manejo de especies amenazadas como para los programas de erradicación de especies invasoras. Los perros usados para la conservación proporcionan una herramienta de censo olfativo que presenta algunas ventajas sobre las técnicas de censos visuales y auditivos usados para algunas especies crípticas. Identificamos cinco medidas importantes para la evaluación del uso de perros a partir de la literatura: precisión, sensibilidad, esfuerzo, costo y comparación con otras técnicas. Exploramos la escala a la cual se evalúa el desempeño y examinamos cuando son alcanzables las pruebas de campo bajo condiciones de trabajo reales. Examinamos 61 estudios publicados entre 1976 y 2018, los cuales reportaron sobre el desempeño de los perros para la conservación y consideramos las incongruencias en el reporte del desempeño de perros de olfato entre estos estudios. La mayoría de los estudios reportaron los tres aspectos necesarios para la evaluación del desempeño: precisión, sensibilidad y esfuerzo. Aunque 43 estudios consideraron al esfuerzo, los métodos incongruentes y el reporte incompleto impidieron una evaluación significativa del desempeño y una comparación entre los estudios. Las diferencias en el costo entre estudios similares estuvieron influenciadas por la ubicación geográfica y cómo el perro y su adiestrador fueron seleccionados para el estudio. Para desarrollar un reporte coherente para la evaluación, recomendamos la adopción de la sensibilidad la precisión y el esfuerzo como medidas estandarizadas del desempeño. Recomendamos que se reporte el esfuerzo como el área y el tiempo invertido en la búsqueda y la precisión como las proporciones del tamaño de la muestra. Además, el reporte de los costos, los objetivos de los censos, el entrenamiento y experiencia del perro, el tipo de labor de detección y la influencia humana proporcionarán mejores oportunidades para comparar dentro de un estudio o entre los estudios.